Unveiling Psychological Drivers of Retirement Planning: Mediating Role of Retirement Goal Clarity - Adhikari, Madhav; Ghimire, Dinesh Mani; Adhikari, Sangam (Journal of Emerging Management Studies, 2025)
Purpose – This paper aims to investigate how factors such as attitude toward retirement, financial risk tolerance, financial self-efficacy, future time perspective, and social group support influence individuals’ retirement planning. Furthermore, the study examines the mediating role of retirement goal clarity in linking these psychological factors to retirement planning behaviors.Design/methodology/approach – This paper employed a descriptive and causal research design to investigate the psychological determinants of retirement planning behavior. Structured questionnaires were used to collect data from 426 salaried professionals working in the service sector of the Kathmandu Valley. A purposive sampling method was adopted to ensure the selection of respondents relevant to the study objectives.Findings – The results reveal that psychological determinants—including attitude toward retirement, financial risk tolerance, financial self-efficacy, future time perspective, and social group support—have significant impacts on retirement planning behavior. Notably, retirement goal clarity was found to play a mediating role, strengthening the relationships between these psychological factors and individuals’ retirement planning actions.Conclusion – This paper underscores the critical influence of psychological factors on retirement planning behavior among salaried professionals. The findings highlight not only the direct effects of these determinants but also the central role of retirement goal clarity in shaping effective retirement preparation. These insights contribute to a deeper understanding of how individuals in developing economies approach retirement planning and offer valuable directions for improving financial preparedness.Implication – The results provide actionable insights for financial advisors, policymakers, and educators. By integrating psychological considerations into workplace training and financial education programs, stakeholders can design tailored interventions that promote retirement goal clarity and enhance financial preparedness. Such initiatives are especially crucial in developing economies, where structured support for retirement planning is often limited.Originality/value – This paper offers a novel contribution by examining the financial planning behavior of salaried professionals within the context of a developing economy—an area often underexplored in the literature. The study presents a comprehensive framework for enhancing retirement planning through targeted educational and policy interventions.